APPLICATION OF INVENTORY ACCOUNTING INFORMATION SYSTEM APPLICATION TO MSMES FILO CR MALANG: PENERAPAN APLIKASI SISTEM INFORMASI AKUNTANSI PERSEDIAAN PADA UMKM FILO CR MALANG - Anik Kusmintarti; Nurafni Eltivia; Aldo Wicaksono Wibowo (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
Nowadays, accounting information systems are needed, significantly to help the business processes of MSMEs. However, technology-based recording is still very rarely found on the scale of MSME businesses such as Filo CR Malang, which until now has not implemented accounting information technology. The purpose of this research is to implement the needs of the Inventory Accounting Information System Application and Design an Inventory Accounting Information System Application to Improve Web-based Internal Control at MSMEs Filo CR Malang. This research is a research and development study through the stages of analysis, design, development, implementation, and evaluation. Microsoft Office, bizagi Modeller, Google Chrome web browser, Draw.io, and Figma are used. The result of the research is in the form of an Inventory Accounting Information System Application to Improve Internal Control at UMKM Filo CR Malang. The development of the implementation of this application at MSME Filo CR is expected to provide solutions and contribute to the control of coffee raw material inventory in accordance with the criteria for production and the quality of accountable and transparent financial reports